Renewable Energy and Nonrenewable Energy Consumption, Co2 Emissions and Economic Expansion Nexus: Further Evidence from Kenya - Mose, Naftaly Gisore (Energy Economics Letters, 2017)
This research scrutinizes economic expansion, CO2 emissions and energy utilization relationship in Kenya by using FMOLS estimate. This study considers the causality matters among oil (Non renewable), electricity (Renewable) use, CO2 emissions, and GDP growth in Kenya by employing time series techniques and annual data for the period 1980–2017. The obtained empirical results from this study indicate that CO2 emissions and electricity effect negatively economic expansion while oil consumption affects it positively. The Granger-causality test conclude that there is no causal relationship running from economic expansion to CO2 emissions, which means that economic expansion can continue without escalating CO2 discharge. However, the study finds unidirectional causality running from economic expansion to oil, and electricity energy use, which implies that Kenya should make an effort to triumph over the constraint on oil and electricity utilization to achieve economic expansion.